The Use of Video as a Media to Improve Students’ Ability on English at SMPN 1 Kebun Tebu - Sherina Maura Amanah; Pratnyawati NuridiSuwarso (Universitas Pahlawan Tuanku Tambusai, 2022)
A great trend toward the use of technology and its integration into the curriculum has acquired great importance. Video has beenused as one of the best resources for students to practice English.Therefore, this study was conducted to investigate the problems during the learning process of using videos, and to find out whether videos can improve the learning outcomes of students in SMPN 1 Kebun Tebu. Classroom Action Research was used to be implemented for the 30 students of SMPN 1 Kebun Tebu. Observation, Pre- and Post-test was used to collect the data. The result refield that there are significance improvement of the students score after having video as the learning media and it showed several challenges faced by the teacher during the learning process. In this case, teachers should be able to choose a suitable video, use technical equipment, and present it in a more interesting and meaningful way.